Crystal structure of human interferon-γ receptor 2 reveals the structural basis for receptor specificity - Mikulecký, Pavel; Zahradník, Jirí; Kolenko, Petr; Černý, Jiří; Charnavets, Tatsiana; Kolářová, Lucie; Nečasová, Iva; Pham, Phuong Ngoc; Schneider, Bohdan (Acta crystallographica. Section D, Structural biology, 2016)
Interferon-γ receptor 2 is a cell-surface receptor that is required for interferon-γ signalling and therefore plays a critical immunoregulatory role in innate and adaptive immunity against viral and also bacterial and protozoal infections. A crystal structure of the extracellular part of human interferon-γ receptor 2 (IFNγR2) was solved by molecular replacement at 1.8 Å resolution. Similar to other class 2 receptors, IFNγR2 has two fibronectin type III domains. The characteristic structural features of IFNγR2 are concentrated in its N-terminal domain: an extensive π-cation motif of stacked residues KWRWRH, a NAG-W-NAG sandwich (where NAG stands for N-acetyl-D-glucosamine) and finally a helix formed by residues 78-85, which is unique among class 2 receptors. Mass spectrometry and mutational analyses showed the importance of N-linked glycosylation to the stability of the protein and confirmed the presence of two disulfide bonds. Structure-based bioinformatic analysis revealed independent evolutionary behaviour of both receptor domains and, together with multiple sequence alignment, identified putative binding sites for interferon-γ and receptor 1, the ligands of IFNγR2.
Keywords: Amino Acid Motifs; Protein Stability; interferon-γ receptor 2; krystalografie rentgenová; Protein Folding; Receptors, Interferon; stabilita proteinů; class 2 cytokine receptors; aminokyselinové motivy; Disulfides; sbalování proteinů; fibronectin type III domain; molekulární modely; Crystallography, X-Ray; proteinové domény; Models, Molecular; receptory interferonů; lidé; konformace proteinů; Humans; Protein Conformation; disulfidy; glykosylace; Protein Domains; Glycosylation